THE ROLE AND IMPORTANCE OF THE NEIGHBORHOOD (MAHALLA) INSTITUTE IN THE CONSTRUCTION OF CIVIL SOCIETY IN UZBEKISTAN (American Journal of Interdisciplinary Research and Development, 2023)
In the article, the role and importance of the neighborhood institute in the construction of civil society in Uzbekistan is revealed with the help of scientific literature and articles in periodicals. In addition, the issues of increasing the role of citizens' self-government bodies in the effective resolution of issues of local importance, as well as the realization of the right of citizens to join an association representing the common interests of citizens' gatherings were also analyzed.